Bioassay-guided isolation of Poliovirus-inhibiting constituents from Zephyranthes candida. (28th November 2014) - Oluyemisi, Ogbole Omonike; Oriabure, Ajaiyeoba Edith; Adekunle, Adeniji J.; Ramsay, Kamdem Soup T.; Shyyaula, Sajan; Choudhary, Muhammad Iqbal
Abstract: Context : Plants of the Zephyranthes genus are globally used in folk medicine. In a previous study, Zephyranthes candida Linn. (Amaryllidaceae) was identified as having antiviral properties; this led to anti-poliovirus assay-guided isolation of compounds from crude methanol extract of the plant. Objective : Isolation of anti-poliovirus constituents from Z. candida . Material and methods : Active chloroform fraction from crude methanol extract of Z. candida (whole plant) was subjected to bioassay-guided fractionation; repeated column and preparative thin layer chromatography led to isolation of active compounds. Chemical structures were identified using spectroscopic techniques. Using serial two-fold dilution of maximum non-toxic concentration (MNTC) of each compound (0.0625–1 µg/mL for lycorine and 0.625–10 µg/mL for trisphaeridine and 7-hydroxy-3′, 4′-methylenedioxyflavan), the ability of extracts to inhibit viral-induced cell death in tissue culture was evaluated 72 h post-infection by the colorimetric method using MTT (3-[4, 5-dimethylthiazol–2-yl]-2, 5-diphenyltetrazolium bromide) dye. Regression analysis was used to determine 50% inhibitory concentration (IC50 ) and 50% cytotoxicity concentration (CC50 ), from which selective index (SI) was calculated. Results : From the chloroform fraction, three compounds were isolated and identified, namely lycorine (1 ), trisphaeridine (2 ), and 7-hydroxy-3′, 4′-methylenedioxyflavan (3 ) as the anti-polioviral components. Lycorine was the most active, with an IC50 value of 0.058 µg/mL followed by trisphaeridine (2 ) with an IC50 of 0.1427 µg/mL, and 7-hydroxy-3′, 4′-methylenedioxyflavan (3 ) with an IC50 of 0.2384 µg/mL. Discussions and conclusions : The antipoliovirus activity of trisphaeridine (2 ) and 7-hydroxy-3′, 4′-methylenedioxyflavan (3 ) is established in this report; these compounds are of moderate toxicity and have very good SI. They could be a potential template for the development of a new antiviral agent.